Efektivitas Suplementasi Antosianin Bunga Telang (Clitoria ternatea L.) dalam Pakan terhadap Peningkatan Intensitas Warna dan Jumlah Sel Kromatofor pada Ikan Cupang (Betta sp.) - Khaira, Ainal; Anhar, Teuku Faizul; Handayani, Lia (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Betta fish (Betta sp.) are one of the most popular ornamental fish species, renowned for their vibrant and striking body coloration. The brightness and intensity of their color are influenced by the number and activity of chromatophore cells, which can be enhanced through dietary pigment supplementation. This study aimed to evaluate the effects of dietary anthocyanin extract from butterfly pea flowers (Clitoria ternatea L.) on color intensity and chromatophore cell count in red, blue, and multicolor betta fish. The experiment employed six treatments with two replicates each: three groups were fed anthocyanin-enriched diets (AA, BB, CC), while three control groups (A, B, C) received diets without anthocyanins. Observed parameters included chromatophore cell histology analyzed microscopically and color intensity measured using the Toca Color Finder (TCF). After 50 days of feeding, results showed a significant increase (P<0.05) in both chromatophore count and body color brightness in fish fed with anthocyanin. The BB group (blue betta+anthocyanin) showed the highest improvement, reaching 209 chromatophore cells compared to 110 cells in the non-anthocyanin control. Sensory scores of coloration also showed significant improvement from day 30 to day 50. These findings indicate that anthocyanins from butterfly pea flowers are effective in enhancing the coloration quality of betta fish, with the most pronounced response observed in blue-colored individuals. Thus, butterfly pea anthocyanins hold potential as natural color enhancers in ornamental fish diets, contributing to improved aesthetic value and marketability.